THE ROLE OF THE QURAN IN THE DEVELOPMENT OF ISLAMIC CIVILISATION AND CULTURE - Nur Faiz Habibah; Taufik Setyaudin; Jakaria (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This study aims to explore the influence of the Quran on the development of Islamic civilisation and culture using the literature research method. Through critical analysis of a wide range of secondary sources including historical books, academic journals, scholarly articles, as well as classical and contemporary interpretations of scholars, this research has collected and evaluated scholarly evidence regarding the contributions of the Quran in the fields of science, law, art, and architecture. The research method involved selecting relevant literature, collecting data, identifying key themes, and synthesising the findings to provide a comprehensive overview of the topic. The results show that the Quran played a significant role in shaping the intellectual and normative framework of scientific and cultural progress in the Islamic world. The golden era of Islam was characterised by great advances in mathematics, medicine, astronomy, and philosophy that were triggered by the Quranic motivation to study and understand the universe. In the social and cultural context, the Quran influenced laws, government policies, and societal values with the principles of justice, equality, and the pursuit of beauty. Furthermore, this study notes how the sustainability and adaptation of these values continue to influence modern Islamic society.